Reflections from psychoanalysis regarding today's environmental challenges. About the book “Desafíos y perspectivas de la situación ambiental en el Perú” - Hernández Camarero, Max (2023)
In relation to the book "Desafíos y perspectivas de la situación ambiental en el Perú: en el marco de la conmemoración de los 200 años de vida republicana," edited by Augusto Castro and María Isabel Merino Gómez and published by INTE-PUCP, this article presents contributions from various authors who address the challenges of climate change from a social and psychoanalytic perspective. Taking up Sally Weintrobe's words, facing climate change is not a technical or scientific problem; it is a human problem, and to address it, it is necessary to take into account individual and community psychological variables.